Primary ST changes. Diagnostic aid in paced patients with acute myocardial infarction. Issue 5 (May 1977) - Niremberg, V; Amikam, S; Roguin, N; Pelled, B; Riss, E
Abstract : In 34 out of 36 patients with apical right ventricular endocardial pacing, primary ischaemic ST alterations were observed during the early stage of acute myocardial infarction. These ST changes, indicating acute injury, were detected in the paced beats in inferior and in anterior infarct. The primary ST changes were consistent only during the early stages of acute myocardial infarction and were not detected when the electrode tip was not in the apex of the right ventricle. It is suggested that the primary ST changes should be used to diagnose acute myocardial infarction in paced patients.